ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGGELAPAN PAJAK - Kasih, Venesia; Ngadiman, Ngadiman (Jurnal Paradigma Akuntansi, 2024)
This study was conducted to know the influence of the Self-Assessment System, Money Ethics and Tax Morale against Tax Evasion. The research sample used in this study was 100 taxpayers who met the sample criteria. The results of the study found that the Self-Assessment System had no effect on Tax Evasion. Money Ethics shows a positive and significant effect on Tax Evasion, while Tax Morale has a negative and significant effect on Tax Evasion. The technique of collecting data used is by distributing questionnaires to taxpayers who are domiciled in Jakarta, have used DJP Online, and have a TIN. The sampling technique used was the Purposive Sampling technique. Data processing using SmartPLS version 3.3.9. The results of the study found that the Self-Assessment System had not affect on Tax Evasion. Money Ethics shows a positive and significant effect on Tax Evasion, while Tax Morale had a negative and significant affect on Tax Evasion.